2010
DOI: 10.1017/s0025315410001712
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of abnormal sexual dimorphic structures in the gonochoristic crustacean, Upogebia major (Thalassinidea: Decapoda), inhabiting mud tidal flats in Japan

Abstract: Normal females of the mud shrimp, Upogebia major, have a pair of pleopods on the first abdominal segment, while normal males do not. We have investigated nine populations in the Seto-Inland Sea, Japan, and found morphological disorders on the first abdominal segments of both males and females. In males, the first pleopods occurred. Morphology and arrangement of these additional pleopods were classified into four types. The pleopods of Types M-1 and M-2 were similar in structure to those of normal females. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
(50 reference statements)
1
8
0
1
Order By: Relevance
“…In accordance with previous studies carried out on various species (Gonor 1972, Roff 1983, Stoltz et al 2005, Nanri et al 2011, the gonads of Paracentrotus lividus can grow at a different rate than its body, and this process may vary between populations. While in Ardeleiro the gonads increased in size at the same rate as the diameter, the gonadal growth in the population of Queiruga was much slower.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance with previous studies carried out on various species (Gonor 1972, Roff 1983, Stoltz et al 2005, Nanri et al 2011, the gonads of Paracentrotus lividus can grow at a different rate than its body, and this process may vary between populations. While in Ardeleiro the gonads increased in size at the same rate as the diameter, the gonadal growth in the population of Queiruga was much slower.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, this index assumes the relationship between the 2 measures is isometric, meaning that both the gonad and body weight increase at the same rate. Consequently, we will refer to this index as the linear gonad index (LGI): (1) Most previous studies that use the LGI assume that these statements are true without first verifying them, even though they have been shown to be false for several marine species (Russell 1998, Stoltz et al 2005, Nanri et al 2011. In these cases, the LGI, or any other GI that assumes isometric gonad growth, should not be used to compare individuals with different sizes, since it could lead to erroneous conclusions about their reproductive cycle (Devlaming et al 1982, Erickson et al 1985, Bonardelli and Himmelman 1995, Somarakis et al 2004.…”
Section: Abstract: Gonad Index · Reproduction · Allometry · Size Effmentioning
confidence: 99%
“…This phenomenon was observed by Kang et al () in Upogebia major . Nanri et al () also observed an ovotestis gonad in U. major , as well as some morphological disorders in the pleopods and dimorphic sexual structures, finding female attributes in males and male attributes in females.…”
Section: Discussionmentioning
confidence: 91%
“…The limitation for mating maybe would occur even for Callianassids under high densities because only a limited number of individuals are available surrounding any single individual with a solitary underground habit. It has been reported in the literature that species with this cryptic lifestyle can present a low population density in their burrows ( C. major = 6.07 galleries/m 2 ) and may display characteristics of intersexuality and hermaphroditism (Almeida & Buckup, ; Botter‐Carvalho, Santos, & Carvalho, ; Kang et al, ; Nanri et al, ; Oliveira et al, ; Rudolph, ; Rudolph & Almeida, ; Rudolph & Verdi, ; Silva‐Castiglioni et al, ). In addition, the occurrence of these characteristics in genus Callichirus is described by Hernáez Bové () and Souza et al () for C. seilacheri and C. major , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation